Estratégias de atenção aos cuidadores informais de idosos: pesquisa participante baseada na comunidade - Borges, Cristiane José (2017)
INTRODUCTION: The process of population aging is a worldwide phenomenon and, simultaneously, a new social role emerges - the informal caregiver-, seen as an essential component to promote elderly’s quality of life in some dependency situation at home. OBJECTIVE: To describe the construction and implementation of care and support strategies for elderlies’ informal caregivers through the Community Based Participatory Research. METHOD: A descriptive study guided by Community Based Participatory Research (CBPR) principles and carried out through the organization of a Community Advisory Committee (CAC), which involved academic and community participants. The study was attended by 384 people, nine community partners, 255 professionals working in family health strategies and 120 elderlies’ informal caregivers. The research was divided into the following phases: 1 - establishment of the community partnership; 2 - identification of problems related to elderly’s informal caregiver; 3 - prioritization of problems related to elderly’s informal caregiver; 4 - capacity survey of community strengths, dynamics and resources; 5 – arrangement of strategies, method, support and care interventions to elderly’s informal caregiver; 6 - implementation of strategies, method, support and care interventions to elderly’s informal caregiver; 7 - data analysis by CAC members; 8- dissemination of results obtained with CAC partnership; 9 - maintenance, CAC sustainability and partnerships evaluation. For the results’ analytical process, the content analysis proposed by Bardin was used for qualitative data and the descriptive statistical analysis was used for quantitative data. The Bioecological Theory of Human Development was adopted as a complementary basis for data analysis. RESULTS: Through the CAC constitution, there were identified, in a collective way, 17 problems faced in the elderly’s informal caregiver daily life. The use of the Severity, Urgency and Trend matrix allowed these problems prioritization for decision making. This process mobilized the construction of an action plan composed by five strategies: 1 - teaching of CAC members about the concepts recommended to define the caregiver role; 2 -raising the knowledge of Family Health Strategy professionals about the importance of including the informal caregiver as a care focus; 3 - performance of the 1st Multiprofessional Care Meeting for Elderly and Informal Caregiver; 4 - recording of the city’s informal caregivers of elderly people; 5 - qualification of the elderlies’ informal caregivers. CONCLUSION: The use of Community Based Participatory Research enabled the community partners’ empowerment, that mobilized themselves in support of elderlies’ informal caregivers, developing actions that included the mapping of the city’s informal caregivers of elderly people, mobilization and qualification of the Family Health Strategy professionals, and the organization of care spaces. In this process, it was verified that this research approach strengthens health democratization by promoting greater involvement and social protagonism of community partners, creating ideas and concrete actions for the establishment of care strategies for the elderlies’ informal caregivers.